The relation between preparation, microstructure and mechanical properties of alumina ceramics - Dela Cuesta, L.; Mena, M.; Sison, G.N.; Bernardo, S.; Cho, S.J.; Uematsu, K.
The starting alumina powders were synthesized by chemical method under varied pH conditions- pH 6.5 and pH 8.5. The resulting powders were characterized by fine particle sizes, high surface area and crystalline structure. Powders at pH 8.5 were noted to have finer particle size than at pH 6.5. Due to their fine characteristic, the powders agglomerated during preparation of compacts. The alumina compacts were fabricated by (1) cold isostatic press (CIP) and sintered at 1550℃ and 1650℃ and (2) hot isostatic process (HIP) and also sintered at 1550℃ and 1650℃. The CIP compacts showed large grains of alumina, whereas the HIP compacts were relatively fine grained. The microstructure of both compacts exhibited abnormal growth more particularly in the CIP compacts. The synthesized powders were contaminated with Ca which accounted for the abnormal grain growth in both alumina compacts. The CA present in HIP fabricated alumina compacts at pH 8.5 and sintered at 1650℃, gave high flexural strength. This was due to the formation of fine elongated grains of regular pattern in between the fine grains in the alumina matrix. The Ca present in the CIP fabricated alumina compacts at pH 8.5 and sintered at 1650℃ gave relatively low values of flexural strength. Flexural strength of alumina compacts fabricated by HIP at pH 8.5 significantly increased with an increase in sintering temperature. For HIP alumina compacts at pH 8.5, fracture toughness increased with an increase in sintering temperature. Such increase in toughness was due to the growth of needle like grains.
Keywords: Aluminum oxide -- Microstructure; Cold isostatic press (CIP).; Hot isostatic process (HIP).